ECONOMICS ANALYSIS OF MAIZE MARKETING IN SURULERE LOCAL GOVERNMENT, AREA IN OYO STATE - AKINNIRAN, Nuraeni Taiwo (Advances in Social Sciences Research Journal, 2018)
ABSTRACT The main objective of this research work was to analyze the economic analysis of maize marketing in Surulere Local Government Area of Oyo-State. The data were collected with the aid of a well structured questionnaire and were later analyzed. About half of the maize marketers (49.9%) had their age between 31-40 years in the study area, most of the maize marketers (80%) are female, while more than half of the maize marketers (60.8%) are married, and 63.3% of the respondents had no schooling experience. Again, high proportion of the marketers had experience less than 10years. For the maize marketers selling price, the significant variables include, age, educational level, major occupation, cost of shop, sellers association and they all have positive relationship with selling price. Barrier to entry and cost of loading. The age, educational level, major occupation, cost of shop and cost of loading are significant at 1% level of significance, while sellers association and barrier to entry are significant at 5% level. An adjusted R2 value of 0.549 which implies that the regression equation accounted for 54.9% of the independent variable like age, educational level, major occupation, cost of shop and cost of loading while the remaining 45.1 percent is an accounted for which might be due to error embedded in the data itself. From the result of the study, the value of Fcal>Ftab. It is therefore concluded that there is a significant relationship between the socio-economic characteristics of the maize marketers and selling price and there is a significant relationship between cost and selling price. Keywords: Economic analysis, Marketing, Cost, Model, Maize